Expression pattern and function analyses of the MADS thranscription factor genes in wheat (Triticum aestivum L.) under phosphorus-starvation condition - Shu-ya SHI; Fei-fei ZHANG; Si GAO; Kai XIAO (Journal of Integrative Agriculture)
MADS-box (MADS) transcription factors (TFs) act as one of the largest TF families in plants. The members in this family play fundamental roles in almost every developmental process as well as involve plant responses to biotic and abiotic stresses. In this study, 54 of MADS genes in wheat, including 31 released publicly and 23 deposited as tentative consensus (TC) into GenBank database, were subjected to analyses of molecular characterization, expression pattern, and function under contrasting phosphate (Pi)-supply conditions. The 31 released MADS genes share cDNA full lengths of 683 to 1 297 bp, encoding amino acids of 170 to 274 aa that possess molecular weights of 19.21 to 31.33 kDa and isoelectric points of 5.74 to 9.63. Phylogenetic analysis categoried these wheat MADS genes into four subgroups containing 11, 5, 10, and 4 members, respectively. Under Pi sufficiency, the MADS genes showed drastically varied transcripts and they were categoried into expression groups of high, medium, low, and very low, respectively. Among them, several ones were differentially expressed under Pi deprivation, including that five were upregulated (TaMADS51, TaMADS4, TaMADS5, TaMADS6, and TaMADS18) and four were downregulated (TaMADAGL17, TaMADAGL2, TaMADWM31C, and TaMADS;14). qPCR analyses confirmed their expression patterns in responding to the Pi-starvation stress. TaMADS51, one of the upregulated genes by Pi deprivation, was subjected to the functional analysis in mediating plant tolerance to the Pi-starvation stress. The transgenic tobocco plants overexpressing TaMADS51 exhibited much more improved growth features, drymass, Pi acquisition, and photosynthetic parameters as well as antioxidant enzymatic activities under Pi deprivation than wild type. These results indicate that distinct MADS genes are transcriptional response to Pi deprivation and play critical roles in mediating plant tolerance to this stressor through regulating downstream Pi-responsive genes.